NAMA Members' Perceptions of Corporate Social Responsibility - Lacy M. Muntean; Traci L. Naile; Greer Gill (Journal of Applied Communications, 2013)
As corporate social responsibility becomes increasingly important within organizations, it is imperative that professionals define their role in setting the CSR agenda. Through a descriptive survey, this study investigated National Agri-Marketing Association members’ perceptions of their roles in CSR and acceptable practices for releasing data about an organization. Respondents were neutral that the agricultural communications industry has a clear code of ethics and standards of performance. NAMA members agreed that developing programs that are good for society is both good for business and good citizenship, and that public relations professionals should be deeply involved in helping management define an organization’s social role. A majority of respondents reported working for an organization that recruited and hired employees who had an agricultural communications major, and had worked with someone who had an agricultural communications major, but were unsure of their preparation, management skills, and strategic thinking skills. Agricultural communications programs should take this perception into account and incorporate these three issues into their curriculum. No research was found that discussed CSR and public relations in the agriculture industry. With this study, agricultural public relations practitioners might see their role in CSR and the need for a clear code of ethics to unify the industry. This study creates a foundation for additional studies of agricultural public relations professionals, delving deeper into more specific roles related to CSR.
Keywords: corporate social responsibility; public relations; agricultural communications; National Agri-Marketing Association; business